The influence of milking procedures on cow’s teat tissue, milk yield and milking time - Saša Špoljar; Alen Džidić; Miroslav Kapš; Jasmina Havranek; Neven Antunac (Mljekarstvo)
The aim of this study was to evaluate the effect of two different milking procedures on teat length and diameter, milk yield and milking time. During the first milking procedure the milker decides when to remove the milking cluster from the udder, while in the second an automatic cluster removal, when milk flow was lower than 200 g/min, was performed. Measurements were made on two commercial farms B and A on 15 randomly chosen cows without any clinical sign of mastitis. There were no significant differencesbetween those farms in teat length and diameter differences before and after the milking. Average milking time on farm A was 6 min and 58 s, while on farm B was 5 min and 3 s. Average milk yield was 12.9 kg on farm B and 13.4 kg on farm A. Milking time was considerably shorter on farm B compared to farm A, while milk yield was almost equal on both farms. Automatic cluster weighting 2 kg removal was performed when milk flow was lower than 200 g/min in order to shorten the time needed to milk the cow, ensuring good udder health.